Sustainable Food House Area Development Strategy (KRPL) Agribusiness based in West Tomohon District, Tomohon City - Wariki , Barce Andries Feriano; Paat, Frangky (Sam Ratulangi University, 2024)
This research aims to determine the strengths, weaknesses, opportunities, threats, and strategies in developing the Food House Area in West Tomohon District, Tomohon City. The research method is the research time from January to April 2023. The data used consists of primary and secondary data. Primary data was obtained from experts, decision-makers, and the public. Secondary data was obtained from related agencies: the Agriculture Service, Food Service, District Office, and Village Office. Sampling was carried out through purposive sampling consisting of 4 respondents, namely the Head of the Agriculture Service, the Head of the Subdistrict, Academics, and people who successfully utilized homestead land. The analysis used consists of Delphi analysis, hierarchy process analysis (AHP), SWOT analysis, and QSPM analysis. The research results show that the influencing factors based on the rating are Yard Land, Labor, Supporting Facilities, business capital, agricultural production facilities, production volume, organic farming, government assistance, product processing, agrarian product marketing, product selling prices pest attacks, and disease. Development strategy in quadrant One which means business expansion strategy. Based on the diversification strategy, the priority is increasing production and marketing. Keywords: area, food, sustainability, yard Abstrak Penelitian ini bertujuan untuk mengetahui faktor kekuatan, kelemahan, peluang dan ancaman serta strategi dalam pengembangan Kawasan Rumah Pangan di Kecamatan Tomohon Barat Kota Tomohon. Metode penelitian yaitu waktu penelitian pada Bulan Januari sampai April Tahun 2023. Data yang digunakan terdiri dari data primer dan sekunder. Data primer diperoleh dari para ahli, pengambil keputusan dan masyarakat. Data sekunder diperoleh dari instansi terkait yaitu Dinas Pertanian, Dinas pangan, Kantor Kecamatan dan Kantor Kelurahan. Pengambilan sampel dilakukan dengan cara purposive sampling yang terdiri dari 4 orang responden yaitu Kepala Dinas Pertanian, Kepala Kelurahan, Akademisi, masyarakat yg sukses dalam pemanfaatan lahan pekarangan. Analisis yang digunakan terdiri dari analisis Delphi, analisys hierarchy prosess (AHP), analisis SWOT dan analisis QSPM. Hasil penelitian menunjukkan faktor-faktor yang berpengaruh berdasarkan ratting yaitu Lahan Pekarangan, Tenaga Kerja, Fasilitas Penunjang, modal usaha, sarana produksi pertanian, jumlah produksi, pertanian organik, bantuan pemerintah, pengolahan hasil, pemasaran hasil pertanian, harga jual produk dan serangan hama dan penyakit. Srategi pengembangan pada kuadran Satu yang berarti strategi ekspansi usaha. Berdasarkan strategi diversifikasi maka yang menjadi prioritas yaitu peningkatan produksi dan pemasaran. Kata kunci: kawasan, pangan, lestari, pekarangan